Photocell with two Schottky barrier contacts Al-p-Siand ohmic silicide contact - R. B. Burlakov (Омский научный вестник)
Way of the fabrication and results of studies of photoelectric features of photocell with two Schottky barrier opaque contacts Al-p-Si on one party of the silicon plate and ohmic silicide contact Ni2 Si-p-Si (or Pd2 Si-p-Si) situated on the opposite party of the plate are сconsidered. It is shown that explored photocell can be used for the transformation of the energy of the radiation in the electrical energy at room temperature in near infrared region of the spectrum (0,8–1,4) micron. This characteristic of the designed photocell will allow to increase its application. Photocell possesses a simple structure and technology with a time of its fabrication in the interval (2,5–3) hour.